G63(P) Parental fever knowledge insufficient for effective care: Opportunities for healthcare professionals. (24th May 2017) - Kelly, M; Sahm, LJ; Shiely, F; O'Sullivan, R; Bont, E de; McGillicuddy, A; Dahly, D; McCarthy, S
Abstract : Aims: Fever, despite being one of the most common childhood symptoms, causes undue concern for parents. The aim of this study was to describe parental knowledge, attitudes and beliefs regarding fever in children aged five years of age and younger. Methods: Ethical approval was granted by the Clinical Research Ethics Committee of the Cork Teaching Hospitals prior to starting the study. Data for this study were collected at purposively selected primary schools in Cork, Ireland using a paper-based survey. Further data were collected from a cross-sectional web-based study using a convenience sample of parents via websites and web pages previously identified in an interview study. The questionnaire administered in this study was developed and used in previous research. Respondent's answers were entered into a data file and analysed using SPSS version 22.0 (SPSS, Inc., Chicago IL). Results: Overall 1104 parents contributed to this research. Almost two thirds of parents (60.4%, n=667) were worried about the consequences of fever in general, while only 27.2% of parents (n=301) were of the opinion that fever may be beneficial to their child's health. Almost two thirds of parents (63.1%, n=695) identified temperatures at which they define fever that were either below or above correct definition of temperature (38OC). Logistic regression analysis showed no apparent associations between reporting the correct definition of fever temperature and years of parenting experience or key socio-demographic factors. Nearly two thirds of parents (64.6%, n=714/1011) alternate between fever reducing medications. Most parents (94.9% n=971) believed that the majority of children with a fever did not need an antibiotic, correspondingly, 71.6% (n=732) believed that there was not always an infection in all fever cases. Conclusion: Parental knowledge concerning fever as a symptom and fever management was found to be deficient. Opportunities to engage with parents when attending healthcare professionals must be used to elucidate what parents already know and to provide parents with relevant and timely information on how to manage the symptom. This could decrease unnecessary presentation at urgent and emergency care services.